DOI: 10.7190/shu-thesis-00015
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated quality management Framework for manufacturing organisations

Abstract: Saad, M.S. and Khamkham, M. (2016). "A conceptual model for successful implementation of lean Six-Sigma for manufacturing organisations".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…However, 244 (92.42%) questionnaires were completed and returned within a given time frame, a response rate (percentage) considered to be very high and acceptable. This is supported by Saunders et al (2009), Khamkham (2017) as they stated that a percentage or response rate needs to be relatively above average. Thus, it is more than enough to receive appropriate feedback to validate and improve the proposed framework and execution procedure.…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, 244 (92.42%) questionnaires were completed and returned within a given time frame, a response rate (percentage) considered to be very high and acceptable. This is supported by Saunders et al (2009), Khamkham (2017) as they stated that a percentage or response rate needs to be relatively above average. Thus, it is more than enough to receive appropriate feedback to validate and improve the proposed framework and execution procedure.…”
Section: Methodsmentioning
confidence: 91%
“…For example, Getachew et al (2017) also considered five human and strategic-oriented common practices such as committed leadership, strategic planning, cross-functional training, employee involvement, information and feedback for successful implementation of synergistic model of TQM and JIT. Hailu et al (2018a) Besides, the quantitative study conducted by Khamkham (2017) confirmed that organization structure, customer focus, training and education, top management and leadership support effective communication, middle management involvement, quality commitment, review and tracking performance are the CSFs for successful execution of the integrated quality management framework, LSS and SS-TQM in particular.…”
Section: Drivers To Application Of Integrated Kaizen Philosophy Frame...mentioning
confidence: 93%
See 3 more Smart Citations